Animal Colonialism: Illustrating Intersections between Animal Studies and Settler Colonial Studies through Diné Horsemanship - John, Kelsey (Humanimalia, 2019)
The objective of this paper is to highlight the relationship between violence against nonhuman animals and Indigenous peoples and, conversely, to reframe the conversation about horses by positioning horses as teachers and knowers for decolonization. I highlight a theoretical and material tension I name: animal colonialism. Animal colonialism is one interlocking tension that centers the interconnected nature of nonhuman animals and humans. I position horses as “knowers,” and as an entry point to understand interconnected Diné ontologies and simultaneously to interrogate multiple binaries which disconnect and erase Indigenous lifeways. To illuminate the conversation on horses, I use a horse lens to reframe the current conversation about free roaming horses on Navajo Nation. Horses and horse relationality is a form of resistance to animal colonialism because it perpetuates a Diné epistemology of connection, resistance, and healing amidst the violence experienced through animal colonialism.